Study of pseudoelastic systems for the design of complex passive dampers: static analysis and modeling. (9th September 2016) - Nespoli, Adelaide; Rigamonti, Daniela; Riva, Marco; Villa, Elena; Passaretti, Francesca
Abstract: This work presents an experimental and numerical analysis of several parallel systems of NiTi pseudoelastic wires. Standard tensile tests were accomplished to evaluate the global damping capacity, the energy dissipated per cycle and the maximum attenuated force in a static condition. Besides, a numerical model was implemented to predict the damping response of more complex pseudoelastic arrangements. It was found a damping capacity upper limit of 0.09 regardless the number and the length of the NiTi components. In addition, it was found that the energy dissipated per cycle is related to the strain and to the number of the NiTi components; furthermore, the system composed of NiTi wires with different length allows for an elastic region that is related to the numbers of wires and that presents a modulation of the stiffness. Finally, the proposed numerical model allows a precise design of complex pseudoelastic combinations as it is able to represent the rhombohedral characteristic.